1998
DOI: 10.1098/rspb.1998.0586
|View full text |Cite
|
Sign up to set email alerts
|

Refuge use by fish as a function of body length–related metabolic expenditure and predation risks

Abstract: Theory predicts that staying in a refuge has bene¢ts in terms of predator avoidance and costs in terms of lost feeding opportunities. In this study, we investigated how the relative importance of these costs and bene¢ts changes with increasing body length. This is of particular interest in animals such as ¢sh, which show continuous growth throughout their lives. Our results suggest that larger ¢sh are subject to lower predation risks and are less a¡ected by food deprivation than small ¢sh, with ¢sh decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
214
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(227 citation statements)
references
References 20 publications
(21 reference statements)
12
214
1
Order By: Relevance
“…Food restriction in animals, for example, leads to an increase, not a decrease, in energy expenditure (Boakes, 2007;Routtenberg and Kusnezov, 1967), and increased rather than decreased risktaking in terms of coming out of cover in the presence of predators (Krause et al, 1998). Food-restricted animals of many different species also switch from preferring less variable to more variable food sources (Caraco et al, 1980;Kacelnik and Bateson, 1996), in line with the predictions of risk-sensitive foraging theory (Stephens, 1981).…”
Section: Introductionsupporting
confidence: 53%
“…Food restriction in animals, for example, leads to an increase, not a decrease, in energy expenditure (Boakes, 2007;Routtenberg and Kusnezov, 1967), and increased rather than decreased risktaking in terms of coming out of cover in the presence of predators (Krause et al, 1998). Food-restricted animals of many different species also switch from preferring less variable to more variable food sources (Caraco et al, 1980;Kacelnik and Bateson, 1996), in line with the predictions of risk-sensitive foraging theory (Stephens, 1981).…”
Section: Introductionsupporting
confidence: 53%
“…fore be able to stay longer in a refuge (Krause et al 1998); thus, we expected 0ϩ roach to move into the vegetation during late summer in the presence of piscivores. This behavior was observed on the last daytime sampling in our study, when no or very few 0ϩ roach were observed outside the vegetation in the piscivore treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It 228 is possible that they were at lower risk because of thelr largcr sizc or bccausc ol bcttcr escape tactics. Small fish usually experience higher predation pressure than larger fish (Sogard 1997) and an indication of this has been f ound in the stickleback with bird predators (Krause et al 1998). However, largc malcs might take larger risks than small males if they have f'ewcr future reproductive opportunities and therefore invest in brceding as a terminal eflbrt (Candolin 1999b).…”
Section: Discussionmentioning
confidence: 99%